Estrategias promocionales para los clientes del Comercial Dismero Fresh - Moncada Balladares, Mariuxi Lizeth (2021)
El commercial Dismero S. A is a company in which its main headquarters is located in the city of Babahoyo, Province of Los Ríos. Thanks to the great reception they have had decide to increase its portfolio of meat products by opening a new branch called Dismero Fresh to provide you with a better service and variety to the customers Babahoyense, but despite this new decision has not obtained the expected effect because many people are unaware of the products offered, because they have not applied the strategies necessary to gain a foothold in the market. That is why there is currently a deficit in sales because no accurate methods have been applied that allow the consumer to know specifically which products are marketed by Dismero Fresh; for this reason very few consume the meat they have for sale because it is this a new product; another drawback is the lack of variety in the product which produces dissatisfaction in the customer who seeks another place to acquire meat products, causing a deficit in sales. Based on the interview applied to the manager of the area it was known that the methods applied are not efficient enough so it leads to a deficit in terms of the sale of their products.